Distribution and habitat of Ocelot (Leopardus pardalis) in Sonora, México - Gallo-Reynoso, Juan Pablo; Van Devender, Thomas R; Rorabaugh, James C; Cirett-Galán, Juan Mario; Villanueva-Gutiérrez, Nora L; Molina-Padilla, Guillermo; Lozano-Angulo, Lydia; Galaz Galaz, J. Manuel; Amador-Alcalá, Saúl A; Silva-Kurumiya, Hugo; Ochoa-Gutiérrez, F. Isaías; Montañez-Armenta, María de la Paz; et al. (THERYA, 2023)
The ocelot (Leopardus pardalis) ranges from northeastern Argentina to southern Texas and southeastern Arizona. It is listed as Endangered in Mexico and the United States. Previous works on ocelots in Sonora, found them occupying different habitats, including tropical deciduous forest, thornscrub, desert grassland, oak woodland, and pine-oak forest, avoiding the driest areas of the Sonoran Desert. The majority of our records are from camera traps, with indirect records from tracks. We analyzed images and videos of more than 100 camera traps used to monitor wildlife in ranches and natural protected areas of Sonora. Cameras were set at an altitude of 70 to 100 cm above ground, some were baited with a sardine-tomato mixture, others were not, the majority were set in areas where other species were the main objective. We obtained 147 recent records from 2015 to 2021 and 28 previous records of ocelots in Sonora. Ocelots occur in the eastern half of Sonora, avoiding areas with less than 400 mm of annual rainfall in the eastern and northwestern Sonoran Desert. Ocelots have been recorded from 53 to 2,151 m elevation (av. 996 m). 21 images in nine localities show females with kittens, indicating breeding populations. In southern and east-central Sonora, ocelots live in tropical deciduous forest, and foothills thornscrub. At Maycoba east of Yécora, in Sierra Huachinera and in the Sky Islands Mountain ranges in northeastern Sonora, ocelots live in temperate vegetation, including desert grassland, oak woodland, and pine-oak forest. Ocelots have been recorded in riparian habitats, transecting other vegetation types in the principal rivers of the state: Ríos Bavispe-Yaqui, Mayo, and Sonora, which drain the Sierra Madre Occidental, the Sky Island Region and southeastern Arizona to the Gulf of California, providing dispersal corridors. Other medium sized rivers provide corridors for the dispersal of ocelots, such as Río Mátape in central Sonora, and Ríos Cocóspera, San Pedro, and Santa Cruz in the north. The nearest Sonoran populations to Arizona are in the Sierra El Alacrán and Río Cocóspera on Rancho El Aribabi.